Uji Tingkat Kesukaan dan Kandungan Gizi Pada Stik Dengan Modifikasi Tepung Kedelai (Glycine Max (L.) Merill) dan Tepung Ikan Wader (Labiobarbus fasciatus) dengan Penambahan Genjer (Limnocharis flava): Evaluation of Consumer Acceptance and Nutritional Content of Sticks Modified with Soybean Flour (Glycine max (L.) Merrill) and Wader Fish Flour (Labiobarbus fasciatus) with the Addition of Genjer (Limnocharis flava) - Novi Nabila Sabrina Sari; Riva Mustika Anugrah; Galeh Septiar Pontang; Puji Afiatna (UNIVERSITAS NGUDI WALUYO, 2026)
Snack sticks are popular ready-to-eat products that can be enriched with nutrients through local ingredients such as soy flour, wader fish flour, and genjer. This study aimed to evaluate their acceptability and nutritional composition. Three formulations were tested: F1 (50% wheat, 25% soy, 20% wader, 5% genjer), F2 (60% wheat, 20% soy, 15% wader, 5% genjer), and F3 (70% wheat, 15% soy, 10% wader, 5% genjer). A hedonic test was conducted with 30 adolescent panelists, and the best formulation was analyzed for energy, protein, fat, carbohydrates, calcium, and fiber using proximate analysis and AAS. Formula F2 achieved the highest acceptance score (79.2%) and contained per 100 g: 510.88 kcal energy, 38.24 g carbohydrates, 24.14 g protein, 29.48 g fat, 221 mg calcium, and 1.95 g fiber. A 40 g serving provides 7.57% of adolescents’ daily carbohydrate needs and meets the snack food criteria of the 2019 Indonesian Dietary Reference Intake. In conclusion, snack sticks made with soy flour, wader fish flour, and genjer showed good acceptability and high nutritional value, making them a potential healthy local-based snack. ABSTRAK Stik merupakan makanan ringan populer yang dapat diperkaya gizi melalui pemanfaatan bahan lokal seperti tepung kedelai, tepung ikan wader, dan genjer. Penelitian ini bertujuan mengevaluasi tingkat kesukaan dan kandungan gizinya. Tiga formulasi diuji: F1 (50% terigu, 25% kedelai, 20% wader, 5% genjer), F2 (60% terigu, 20% kedelai, 15% wader, 5% genjer), dan F3 (70% terigu, 15% kedelai, 10% wader, 5% genjer). Uji hedonik dilakukan pada 30 panelis remaja, sedangkan formula terbaik dianalisis kandungan energi, protein, lemak, karbohidrat, kalsium, dan serat menggunakan metode proksimat dan AAS. Formula F2 memperoleh skor tertinggi (79,2%) dengan kandungan per 100 g: energi 510,88 kkal, karbohidrat 38,24 g, protein 24,14 g, lemak 29,48 g, kalsium 221 mg, serat 1,95 g. Satu sajian (40 g) memenuhi 7,57% kebutuhan karbohidrat harian remaja dan sesuai kriteria makanan selingan AKG 2019. Kesimpulannya, stik berbasis kedelai, ikan wader, dan genjer memiliki daya terima baik serta nilai gizi tinggi sehingga berpotensi sebagai camilan sehat lokal.